Validity of the development of a digital handout on bryophyte diversity based on problem-based learning (PBL) in Tahura Sultan Adam Mandiangin - Siti Maryati; Aulia Ajizah; Amalia Rezeki (HAFECS PRESS, 2025)
The development of digital handouts based on Problem-Based Learning (PBL) is important to improve the quality of contextual, interactive learning, and in accordance with the demands of 21st century skills. Biodiversity such as moss (Bryophyta) can be a direct source of learning in learning Cryptogamae courses that can be packaged as teaching materials in the form of digital moss handouts based on PBL. The development of digital handouts can increase the attractiveness of students and overcome obstacles in learning moss material that is difficult for students. This research and development aim to describe the validity of the developed digital handouts. The teaching material development model used is the ADDIE model which is limited to the development stage. The subjects in the study consisted of material validation tests and media experts. The developed digital handout product obtained a percentage of 91.50% in the material validation test with very valid criteria, 70.40% in the media validation test with valid criteria. Based on these results, the digital handout is suitable for use as a support for the Cryptogamae course on moss material. In addition, this study shows that the PBL model packaged in digital handouts can increase student engagement and understanding of complex materials and can be used as a reference for other digital teaching materials. Abstrak. Pengembangan handout digital berbasis Problem-Based Learning (PBL) penting untuk meningkatkan kualitas pembelajaran yang kontekstual, interaktif, dan sesuai dengan tuntutan keterampilan abad ke-21. Keragaman hayati seperti lumut (Bryophyta) dapat menjadi sumber belajar langsung dalam pembelajaran mata kuliah Cryptogamae yang dapat dikemas sebagai bahan ajar berupa handout digital lumut berbasis PBL. Pengembangan handout digital dapat meningkatkan daya tarik peserta didik dan mengatasi kendala dalam mempelajari materi lumut yang sulit bagi peserta didik. Penelitian dan pengembangan ini bertujuan untuk mendeskripsikan validitas terhadap handout digital yang dikembangkan. Model pengembangan bahan ajar yang digunakan adalah model ADDIE yang dibatasi sampai tahap pengembangan (development). Subyek dalam penelitian terdiri dari uji validasi materi dan media. Produk handout digital yang dikembangkan memperoleh persentase 91,50% pada uji validasi materi dengan sangat valid, 70,40% pada uji validasi media dengan kriteria valid. Berdasarkan hasil tersebut, maka handout digital layak digunakan sebagai penunjang mata kuliah Cryptogamae pada materi lumut. Selain itu, penelitian ini menunjukkan bahwa model PBL yang dikemas dalam handout digital dapat meningkatkan keterlibatan dan pemahaman peserta didik terhadap materi yang kompleks dan dapat menjadi acuan sebagai bahan ajar digital lainnya.